Contemporary Greek Film Cultures from 1990 to the Present - Kazakopoulou, Tania; Fotiou, Mikela (New Studies in European Cinema, 2017)
This collection of new writing on contemporary Greek cinema builds and expands on existing work in the field, providing a coherent analysis of films which, despite their international importance, have so far received limited critical attention. The volume maps key trends in Greek cinema since the 1990s within the wider context of production and consumption at both national and international levels. It offers a wide range of critical analyses of documentary and avant-garde filmmaking, art house and popular cinema, and the work of established and new directors as well as deliberations on teaching methodologies and marketing strategies. The book seeks to highlight the continuities, mutual influences and common contexts that inform, shape and inspire filmmaking in Greece today.
Keywords: 1-Cinéma; 2-Muséologie critique; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé